Numerical analysis of the creep crack constraint effects and the creep crack initiation for pressurized pipelines with circumferential surface cracks. (January 2018) - Wu, Dongquan; Jing, Hongyang; Xu, Lianyong; Zhao, Lei; Han, Yongdian
Highlights: The numerical analysis of the pressurized pipelines with circumferential surface cracks is proposed. The contour integral C* and load-independent constraint parameter Q* along the crack front are investigated. The creep damage accumulations and the CCI times at the positions with the maximum values of C* or Q* are obtained. The influence of the crack geometrical sizes on C*, Q* and CCI times are investigated. Empirical relationships between the CCI times and crack geometrical sizes are proposed. Abstract: The creep crack constraint effects using a load-independent creep constraint parameter Q* and the creep crack initiation (CCI) times were characterized by 3D finite element method for pipelines with circumferential surface cracks of different geometrical sizes. The results revealed that the distribution regulation of Q* along the crack front for circumferential internal surface cracks and external surface cracks was similar. The maximum constraint level occurred near the deepest crack front part for cracks with smaller a/c, while it occurred near the free surface for cracks with larger a/c . The constraint values at the same position (2 Φ/ π) increased with the increasing of the crack depth when a/c kept constant. The circumferential internal surface cracks of pipelines were proved more dangerous than the external surface cracks with the same geometrical size. Furthermore, the CCI times were decided by the peak values of constraint, or the CCI firstly occurred at the position where the constraint level was maximum. In addition, the empirical relationships between the CCI times and crack sizes were fitted, which was also verified effectively.